(untitled) (Modern information system and technologies, 2018)
In the article the essence of the radio-relay communication is considered, and the peculiarities of the signal propagation depending on the atmospheric conditions and the frequency range, modern tendencies and perspectives of the development of the radio-relay communication are described. Keywords: base station, wireless networks, communication range, bandwidth, receiving and transmitting radio stations, radio-relay communication.